Architects of Stalingrad — creators and defenders of the city - Oleynikov, P. P.; Antonova, N. N. (Sot͡s︡iologii͡a︡ goroda, 2025)
The article is devoted to the architects of the city who took part in the design of the city, its protection during the Great Patriotic War and in the post-war renaissance. Previously unknown facts about the involvement of Stalingrad architects in military exploits on the fronts and labor achievements during the peaceful years are considered. The peculiarity of the creative perception of the architects' life experience through the prism of the horrors of war and the implementation of these plans in their projects is noted. The most famous projects and buildings of the period under review are presented